THE USE OF COOPERATIVE LEARNING TO ENHANCE LOW AND HIGH MOTIVATED STUDENTS IN WRITING DESCRIPTIVE TEXT (The Case of Grade Seven Students of SMP Kesatrian 1 Semarang) (English Education Journal, 2014)
Many research projects was conducted to find out more effective techniquesÂ  to teach English.This study was conducted becauseÂ  most of the students at SMP Kesatrian 1 Semarang had some difficulties in descriptive text writing. It was done to give a new experience for them to learn descriptive text by means of cooperative learning to improve the quality of their writing. It employed factorial design 2x2 because it employed more than one independent variable; TPS, CIRC and one dependent variable.The experimental group was given experiences of learning by TPS technique and the control group by CIRC technique. The study was accomplished in the academic year 2013/2014. The samples were two classes, class A, and class C. Class A was the experimental group and class C was the control one. The result of the study proved that both of the techniques were effective to enhance descriptive text writing for students of different levels of motivation. However TPS was more effective than CIRC. The result of the study can be used as the consideration on teaching descriptive text writing for the teachers. It can also be a reference in doing other research by other researchers.